Optimalisasi Alat Gali Muat (Caterpillar 330 GC) dan Alat Angkut (HINO 500 FM 280 JD) Dalam Pengupasan Tanah Penutup di PT. Bhumi Sriwijaya Perdana Coal Sumatera Selatan: Optimization of Loading Digging Equipment (Caterpillar 330 GC) and Transport Equipment (HINO 500 FM 280 JD) in Overburden Stripping at PT. Bhumi Sriwijaya Perdana Coal South Sumatra - Widodo, Krisna (ReTII, 2024)
Bhumi Sriwijaya Perdana Coal is one of the companies engaged in the coal mining sector, experiencing obstacles in achieving the overburden stripping production target. The Company's production target for loading and hauling equipment is 88,000.00 BCM/month. Based on actual results in the field, the target was not achieved. Not achieving production targets at PT. Bhumi Sriwijaya Perdana Coal due to several factors. The problem that occurs today is that the production of loading and hauling equipment has not been optimal so that the production targets set have not been achieved. The purpose of this study is to evaluate obstacles that can affect effective work time due to tools, natural and human factors. As well as optimizing the performance of loading and hauling equipment so that it can affect production targets. The methods used in this study are as follows: Literature study, field observation, data collection based on primary data and secondary data, processing and analysis, as well as conclusions and suggestions. The results showed that the actual yield of Caterpillar 330 GC loading and digging equipment was 53.791,92 BCM/month, and HINO 500 FM 280 JD conveyance was 54.287,24 BCM/month. With effective working time for loading conveying excavation is 15,65 hours / day and transportation equipment is 15,68 hours / day, and tool work efficiency is loading conveying excavation 78% and transportation equipment 79%. The compatibility factor between loading and hauling equipment is 0.66 < MF 1. After analysis is carried out to increase production, by adding bulk filling and optimizing the distribution time of loading digging equipment. Evaluation production results were obtained for Caterpillar 330 GC loading and digging equipment of 89.883,36 BCM/month, and HINO 500 FM 280 JD transportation equipment of 90.086,36 BCM/month. And the compatibility factor of the tool becomes 0.86 MF < 1.